Infrastructure Privatization and Regulation : Promises and Perils - Kessides, Ioannis N. (Oxford University Press on behalf of the World Bank, 2013)
Infrastructure is crucial for generating growth, alleviating poverty, and increasing international competitiveness. For much of the twentieth century and in most countries, the network utilities that delivered infrastructure services such as electricity, natural gas, telecommunications, railroads, and water supply were vertically and horizontally integrated state monopolies. But this approach often resulted in extremely weak services, especially in developing and transition economies and especially for poor people. Common problems included low productivity, high costs, bad quality, insufficient revenue, and shortfalls in investment. Over the past two decades many countries have implemented far-reaching institutional reforms restructuring, privatizing, and establishing new approaches to regulation. This article identifies the challenges involved in this massive policy redirection within the historical, economic, and institutional context of developing and transition economies. It also reviews the outcomes of these policy changes, including their distributional consequences especially for poor households and other disadvantaged groups. Drawing on a range of international experiences and empirical studies, it recommends directions for future reforms and research to improve infrastructure performance.